STUDI LITERATUR MENGENAI PERAN GANDA PADA PEKERJA PEREMPUAN - Arifah Dea Riwinda; Mirwan Surya Perdhana (Diponegoro Journal of Management, 2022)
This study aims to describe dual role conflict in female workers. The problems in this study include the dual role challenges of female workers and how to balance their work and family domain. The purpose of this study is to find out the dual role challenges and solutions on how to balance their work and family domain. This research is a qualitative type of research. An extensive literature review was conducted to gain conclusion on how female workers face the challenges of dual role conflicts and manage to balance their work and family domain. The findings in this study cover two things: The challenges of the dual role of female workers, which include social stigma on female workers; difficulty allocating time between the two roles, and dual roles conflict have negative impact on female workers’ work performance; Strategies to balance between work and family domain which includes social support from family, co-workers, and managerial.